A Narrative Inquiry into School Counseling Management for Students’ Mental Well-Being - Anas Rohman; Kholfan Zubair Taqo Sidqi; Achmad Munib; Erry Nurdianzah; Husen Waedoloh (International Journal of Educational Narratives, 2026)
Background. Guidance and counseling management is a vital component of the educational system, supporting students’ mental health and overall development. Students’ psychological growth is shaped by internal and external factors, including family environment, school conditions, peer relationships, academic pressure, and technological advances. Effective, systematic, and sustainable guidance and counseling services are therefore essential to help students navigate emotional, social, and academic challenges. Purpose. This study analyzes the role of guidance and counseling management in developing students’ mental health at school and examines how effective counseling services contribute to their emotional, social, and academic development. Method. This study employed a qualitative approach using a narrative review method to critically explore the development of guidance and counseling management concepts in relation to students’ mental health. Data were collected from books, journals, and prior studies, then analyzed through content analysis involving data reduction, presentation, interpretation, and conclusion drawing. The review highlights the importance of integrating administrative management with students’ emotional and personal needs to support holistic mental health development. Results. Findings show that effective guidance and counseling management positively contributes to students’ mental health. Counseling services help improve emotional stability, social skills, self-confidence, learning motivation, and problem-solving abilities. Program success depends on proper planning, collaboration among school stakeholders, professional counseling teachers, parental involvement, and a conducive school environment. Evaluation and follow-up activities further strengthen the effectiveness and sustainability of counseling services. Conclusion. Guidance and counseling management plays a significant role in supporting students’ mental health. Through systematic planning, organization, implementation, evaluation, and follow-up, schools can strengthen professional counseling systems to foster students’ optimal emotional, social, and academic development.